Inside IBM : A European's Story - Maisonrouge, Jacques, 1924-; Translation by Nina Rootes (Glasgow Fontana / Collins, 1989)
An autobiographical account of the background and experiences of the President of IBM's World Trade Corporation, born in 1924, in Cachan, south of Paris. He represents a recipe for success for anyone wishing to succeed in the development, management and marketing of a business organization.
Keywords: International business enterprises--Management -- Management